Ethnobotanical Documentation of Medicinal Plants Used by the Indigenous Panay Bukidnon in Lambunao, Iloilo, Philippines - Cordero, Cecilia Salugta; Meve, Ulrich; Alejandro, Grecebio Jonathan Duran (Frontiers in Pharmacology, 2022)
The Panay Bukidnon is a group of indigenous peoples living in the interior highlands of Panay Island, in Western Visayas, Philippines. Little is known about their ethnopharmacological knowledge due to limited written records and no recent research has been conducted on the medicinal plants they used in ethnomedicine. This study aims to document the medicinal plants used by the indigenous Panay Bukidnon in Lambunao, Iloilo, Panay Island. A total of 131 medicinal plant species distributed in 121 genera and 57 families were used to address 91 diseases in 16 different use or disease categories. The family Fabaceae was best represented with 13 species, followed by Lamiaceae with nine species, and Poaceae with eight species. The leaf was the most frequently used plant part and decoction was the most preferred form of preparation. To evaluate the plant importance: use value (UV), relative frequency citation (RFC), informant consensus factor (ICF), and fidelity level (FL) were used. Curcuma longa L. had the highest UV (0.79), Artemisia vulgaris L. had the highest RFC value (0.57), and Annona muricata L. had the highest RI value (0.88). Diseases and symptoms or signs involving the respiratory system and injury, poisoning and certain other consequences of external causes recorded the highest ICF value (0.80). Chromolaena odorata (L.) R.M.King & H.Rob. had the highest FL value (100%) used for cuts and wounds. The results of this study serve as a medium for preserving cultural heritage, ethnopharmacological bases for drug research and discovery, and preserving biological diversity.